Adsorption characteristics and the removal mechanism of two novel Fe-Zn composite modified biochar for Cd(II) in water. (August 2021) - Yang, Tingting; Xu, Yingming; Huang, Qingqing; Sun, Yuebing; Liang, Xuefeng; Wang, Lin; Qin, Xu; Zhao, Lijie
Graphical abstract: Highlights: Two novel Fe/Zn composite modified biochars were prepared. Fe/Zn- BC was effective for Cd(II) removal from water. Precipitation and complexation are the main adsorption mechanisms. Abstract: In this study, adsorbents (Fe/Zn-RBC and Fe/Zn-DBC) for the removal of Cd(II) in water were successfully prepared by iron/zinc composite modified biochar derived from the branches of Robinia pseudoacacia biochar (RBC) and durian shells biochar (DBC). The results revealed that the iron and zinc ions were successfully loaded onto the biochar. The adsorption data of Cd(II) on Fe/Zn-BC conformed to the models of pseudo-second-order kinetic, Langmuir isothermal, and Redlich-Paterson. According to the results of batch experiments, the maximum sorption capacities of Fe/Zn-RBC and Fe/Zn-DBC for Cd(II) were approximately five times and three times higher than RBC and DBC, respectively. As the most dominant adsorption mechanisms, Cd(II) and CO3 2–, Fe-O, Zn-O, and oxygen-containing functional groups on the Fe/Zn-BC surfaces precipitated CdCO3, Cd(OH)2, and CdO. Therefore, Fe/Zn-BC is an excellent adsorbent that removes Cd(II) from aqueous solutions, and also can be used in waste resource utilization, which has potential applications prospects.